(untitled) (Asian Journal of Agriculture, 2017)
Abstract. Nawiri SO, Oduor RO, Jalemba AM. 2017. Genetic engineering of sweet potatoes (Ipomoea batatas) using isopentenyl transferase gene for enhanced drought tolerance. Asian J Agric 1: 85-99. Approximately 70% of yield crop reduction worldwide is caused by drought. Due to severe drought, which happens often as a result of climate change, substantial yield deprivation is usual among the major cereals such as maize, wheat, and barley. Therefore, drought tolerant crops that still yield amidst erratic climatic phenomena are greatly needed. Due to its capability to produce high yield in a short period, sweet potato is suitable for cultivation in regions with limited or erratic rainwater supply where other food crops cannot grow easily. Nevertheless, its sensitivity to water deficit may lead to adverse crop growth and yield. By conventional hybridization method, sweet potato is tried to be improved, but it gives unsatisfied results due to its high male sterility, sexual incompatibility and hexaploidy nature of its genome. The aim of this study, therefore, is to develop new varieties of sweet potato with improved tolerance to water-deficit stress for sustainable production of sweet potato under water-limited conditions. Three sweet potato genotypes: Jewel, Kemb36, and Ksp36 were transformed using isopentenyl transferase gene (IPT) that delays drought-induced senescence via up-regulation of cytokinin biosynthesis, under the control of a water-deficit responsive and maturation specific promoter (PSARK). The PNOV-IPT gene construct was introduced into sweet potatoes to evaluate their transformability and regenerability. It was done via Agrobacterium tumefaciens strain EHA101 and the plants subsequently regenerated via somatic embryogenesis. Jewel genotype recorded the highest transformation and regeneration frequency, followed by Kemb36 and KSP36. Calli were cultured on media supplemented with various mannose concentrations to evaluate the suitability of mannose as a selectable marker for sweet potato, and it was discovered that 30 g/L concentration was optimal for selection of transformed events. At the time of PCR analysis, Jewel had the highest transformation efficiency followed by Kemb36. At the time for evaluation on drought tolerance under controlled conditions, the sweet potato showed delayed senescence and greater drought tolerance under water deficit conditions in the glasshouse. These plants exhibited better growth, higher yield, higher water status maintenance, higher chlorophyll content, and thus higher photosynthetic rates under reduced water conditions in comparison to wild-type. These results, therefore, indicated that expression of isopentenyl transferase gene in sweet potato significantly improves drought tolerance. Therefore, IPT gene should be used to transform other economically important food crops to delay drought-induced senescence and enhance drought tolerance.